2008
DOI: 10.1002/pola.23013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, photopolymerization and adhesive properties of new hydrolytically stable phosphonic acids for dental applications

Abstract: Novel monomers 2-(N-methylacrylamido)ethylphosphonic acid, 6-(Nmethylacrylamido)hexylphosphonic acid, 10-(N-methylacrylamido)decylphosphonic acid, and 4-(N-methylacrylamidomethyl)benzylphosphonic acid have been prepared in good yields for use in dental adhesives. They have been fully characterized by 1 H-NMR, 13 C-NMR, 31 P-NMR, and by HRMS. All monomers are hydrolytically stable in aqueous solution. Free radical homopolymerizations of these monomers have been carried out in solution of ethanol/water (2.5/1:v/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 23 publications
1
66
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] For example, owing to the safety advantages for biological applications as well as in thick section photo-curing, visible-light activated three-component initiator systems have been expanding into application areas such as dental restorative materials, bio-detections, color printing, holographically photopolymerized composites and microencapsulation. [9][10][11][12][13] Three-component initiator systems are very efficient for the production of free radical active centers and tremendously promising for a number of industrial and biomedical applications; however, a potential problem in many of these systems is thermal stability and long-term dark storage stability. 14,15 For practical consideration in all applications, initiator systems must provide adequate shelf-life stability while also producing efficient, rapid polymerization on demand.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] For example, owing to the safety advantages for biological applications as well as in thick section photo-curing, visible-light activated three-component initiator systems have been expanding into application areas such as dental restorative materials, bio-detections, color printing, holographically photopolymerized composites and microencapsulation. [9][10][11][12][13] Three-component initiator systems are very efficient for the production of free radical active centers and tremendously promising for a number of industrial and biomedical applications; however, a potential problem in many of these systems is thermal stability and long-term dark storage stability. 14,15 For practical consideration in all applications, initiator systems must provide adequate shelf-life stability while also producing efficient, rapid polymerization on demand.…”
Section: Introductionmentioning
confidence: 99%
“…Dry THF was purchased from Sigma-Aldrich. Diethyl 2-aminoethylphosphonate 2a, [20] diethyl 6-bromohexylphosphonate, [21] 10-(methacryloyloxy)decylphosphonic acid 10, [22], and N-(2-aminoethyl)methacrylamide 7 [23] were prepared according to the literature. TMSBr (Sigma-Aldrich, Switzerland) was distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…First of all, amine 2a and bromophosphate 5 were prepared according to literature procedures. [20,21] Aminophosphonate 2b was then obtained from phosphonate 5 by a Gabriel synthesis. Bromophosphonate 5 was treated with potassium phthalimide in DMF at 100 °C to provide phthalimide 1b in 72% yield.…”
Section: Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,24] It was also demonstrated that N-alkylacrylamides exhibit a great stability in such acidic conditions. [2,9,10,25] Monomers 4, 8, 10a and 10b bearing a methacrylate group, their storage in aqueous solutions would require low temperatures (storage in the refrigerator). In this context, we took an interest in the synthesis of the monomers 12, 16a and 16b, which exhibit a higher stability in aqueous media (Figure 2).…”
Section: Synthesesmentioning
confidence: 99%